Cervical lymphnode metastasis in oral squamous cell carcinoma: Correlation of manual palpation, ultrasonographic, and histopathological findings - Sathya P Dongade; Mangala Meti; Devara Neela Sundara Venkata Ramesh (Wolters Kluwer Medknow Publications, 2017)
Introduction: The staging of cervical lymphadenopathy is an important consideration in the management of oral cancer as it determines the patients' prognosis. Ultrasound is used to image the cervical lymph nodes for staging because it is noninvasive and there is no radiation exposure to the patient. Aim: To investigate the applicability and diagnostic relevance of sonography in staging cervical lymphnode metastases. Materials and Methods: Cervical lymphnodes of the patients were subjected to manual palpation and ultrasound evaluation for its size, number, shape, borders, internal echoes, echogenic hilus, and central necrosis. The manual palpation findings and ultrasound features of the lymphnodes were compared with the histological features for malignant and nonmalignant nodes. Results: When short axis of node is more than 10 mm, 86% were metastatic, nodes with irregular borders were metastatic in 84%, in the absence of the echogenic hilus, 93% were metastatic, 81% were metastatic with heterogeneous nodes, and nodes with central necrosis showed 90% metastasis. Conclusion: By using ultrasound no single parameter showed high sensitivity, specificity, and accuracy.